Design of PC beam-column joint applied X-braced bars in the segmented structural system - Kim, Sijun; Lee, Seongsoo; Chun, Homin; Hong, Kappyo (Journal of Civil Engineering and Management, 2016)
This study suggests a joint design using an X-brace bar to identify the stability and structural performance of a precast concrete (PC) beam-column joint design, which may cause problems when used in a segmented PC beam system for a long-span structure. For this, an experimental PC beam-column model at half scale was designed and verified for applicability of X-braced bars in a panel zone. While previous studies suggested the development of a long-span structural system using precast concrete (PC) and described the problems with PC beam-column joints, this study proposes a solution to improve the structural stability and performance of a PC beam-column joint design and conducts analytical verification.